Anti-leukemic activity of axitinib against cells harboring the BCR-ABL T315I point mutation - Okabe, Seiichi (J Hematol Oncol, 2015)
The BCR-ABL; breakpoint cluster region-Abelson point mutation T315I is resistant to ABL tyrosine kinase inhibitors. However, axitinib, a vascular endothelial growth factor receptor inhibitor, is effective against this mutation. In this study, we investigated axitinib activity against ponatinib-resistant cells and found that axitinib inhibited cellular growth and apoptosis in Ba/F3 T315I-mutant cells and T315I-mutant primary samples, but not in ponatinib-resistant Ba/F3 cells and primary samples. Thus, an alternative strategy may be required to improve the prognosis of Philadelphia-chromosome-positive leukemia patients harboring BCR-ABL point mutations.